Orbital cellulitis as a complication of odontogenic infection - Puji Yuli Christiani Purba; Melita Sylvyana; Endang Syamsudin; Rani Septrina (Faculty of Dentistry, Universitas Gadjah Mada, 2019)
Orbital cellulitis is uncommon sequelae of the spread of odontogenic infection to adjacent maxillary sinuses or to distant sites such as the orbits. Once it happened, the spread of such infection can be of serious complication such as complete blindness or even more serious and life threatening situations as cavernous sinus thrombosis, intra-cranial abscess, or even death. This paper aimed to expose the guideline treatment of orbital cellulitis as a complication of odontogenic infection. It reported one case of orbital cellulitis in the emergency unit of Hasan Sadikin hospital Bandung, with complaints of pain, swelling at cheek and periorbital region, and the history of toothache. The treatment include incision drainage, extraction of tooth, and parenteral administration of antibiotic and analgesic. Odontogenic infections are derived from dental infection and can potentially spread rapidly to be ascending infection like orbital cellulitis. Odontogenic infection and orbital cellulitis should be adequately treated with incision drainage, extraction of tooth and parenteral administration of antibiotic, steroid and analgesic. Without immediate treatment, odontogenic infection can lead to ascending infection. Orbital cellulitis due to spreading of odontogenic infection is a rare case. In this case report, the patient had a significantimprovement due to immediate and proper treatment.